Economic Burdens for Treatment of Patients With Type 2 Diabetes in North Thailand: A Hospital-Based Observational Study - Phrommintikul, Arintaya; Dilokthornsakul, Piyameth; Permsuwan, Unchalee (Frontiers in Endocrinology, 2022)
Purpose: Diabetes and its complications poses an economic burden to healthcare system, family and society. Therefore, this study aimed to estimate the real world financial burden of type 2 diabetes (T2DM) treatment, complications, and cardiovascular death. Materials and Methods: An electronic database of the largest university affiliated hospital in the North of Thailand was retrieved for a 10-year period (2009-2019). We used the International Classification of Disease 10th Revision (ICD-10) codes of diabetes and complication to obtain relevant patient records. All included records based on the inclusion and exclusion criteria were analyzed. Expenditures of diabetes treatment, complications, and cardiovascular death for two years were reported as mean, standard deviation, median, and interquartile range. Results: Of a total of 9,161 patient records, average age of patients was 57.8±12.7 years. The average total outpatient cost was THB 22,874±38,066 (US 759±1,264) for the first year and THB 23,462±34,441 (US 779±1,143) for the second year. The average inpatient expenditure was THB 160,790±411,607 (US 5,338±13,666) for the first year and THB 181,804±190,257 (US 6,036±6,317) for the second year. Drug was the main component for outpatient expenditure while surgery was the main component for inpatient expenditure. Diabetes patients with complications incurred greater cost of treatment than those without complications. Cardiovascular death led to about seven times higher cost of treatment than average total cost of diabetes treatment. Heart failure complication (THB 846,345±752,884 or US 28,099±24,996) had the greatest inpatient costs compared with other complications in the first year. Stroke complication (THB 71,927±143,414 or US 2,388±4,761) had the greatest outpatient costs compared with other complications. In general, the first year expenditure was higher than the second year for all complications. Conclusions: Diabetes incurs substantial financial burden resulting from its complications. Effective management of diabetes with a multi-sectoral effort from government, providers, patients, and private is required.